Method for preparing C6-C9 liquid oxygen-containing fuel through selective hydrogenolysis of lignin
By doping magnesium oxide-supported ruthenium hydrate catalyst with titanium silicon molecular sieve, adjusting the acid and alkalinity of the catalyst and reducing temperature, the problems of low depolymerization conversion and low product yield during the catalytic hydrogenolysis of lignin are solved, and efficient preparation of lignin depolymerization and high selectivity saturated alcohol products are achieved.
Patent Information
- Application Number
- CN202411857196.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art has problems such as low depolymerization conversion, low product yield and harsh reaction conditions during the catalytic hydrogenolysis of lignin.
The titanium silicon molecular sieve is used to dopant magnesium-supported ruthenium hydrated catalyst to achieve efficient depolymerization of lignin by adjusting the acid and alkalinity of the catalyst and reducing temperature.
The conversion rate of lignin is improved to 92.6-97.8%, the total yield of volatile products is 25.6-36.2%, the total yield of alcohol products is 16.5-20.2%, and the selectivity is 49.5-59.7%. The catalyst preparation process is simplified and energy consumption is reduced.
Smart Images

Figure CN119798031A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to lignin catalytic hydrogenolysis, in particular to a method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin, belonging to the field of high-value utilization of renewable biomass. Background Art
[0002] With the progress of social science and technology and the rapid development of industry, fossil energy such as oil and natural gas has been vigorously exploited and utilized, which has caused energy crisis and a series of environmental problems, such as the intensification of atmospheric greenhouse effect and the deterioration of natural ecological environment. Since the beginning of the 21st century, human beings have been increasingly aware of energy crisis and environmental problems, and are eager to seek new green energy that can be used to replace traditional fossil fuels. As the most abundant biomass resource in nature, lignocellulose is a clean and efficient energy source, and the bio-liquid oxygen-containing fuel prepared from it is expected to become an ideal substitute for traditional fossil fuels.
[0003] Lignocellulose is composed of cellulose, hemicellulose and lignin. In general wood plants, cellulose accounts for 35-50%, hemicellulose accounts for 25-30%, and lignin accounts for 15-30%. Lignin is an aromatic amorphous biomacromolecule with a high degree of polymerization, which is composed of three phenylpropane basic structural units randomly and disorderly bonded by CO bonds and CC bonds. The molecule contains a variety of oxygen-containing functional groups such as methoxy, carbonyl, and hydroxyl groups and a large number of carbon-carbon unsaturated double bonds. Due to its complex chemical structure, amorphous shape and high condensation degree, lignin is more difficult to degrade than general carbohydrates, which is a huge challenge for the purification, separation and further utilization of lignin.
[0004] Lignin catalytic hydrogenolysis, also known as catalytic reduction depolymerization, refers to the reduction reaction of lignin under the action of an external hydrogen source and a catalyst, which promotes the breaking of its CO and CC chemical bonds, thereby increasing the yield of soluble depolymerization products of lignin. Compared with other depolymerization methods, catalytic hydrogenolysis has the characteristics of relatively mild reaction conditions and relatively concentrated distribution of depolymerization products. In addition, the hydrogenolysis products have significant advantages such as low unsaturation, low oxygen content, high hydrogen-to-carbon ratio, and high calorific value. It is a very promising lignin depolymerization method. The pore structure and acidity and alkalinity of the catalyst significantly affect its hydrogenolysis activity for lignin. Therefore, designing a catalyst with multi-level pores and suitable acidity and alkalinity is the key point of the lignin catalytic hydrogenolysis system. Molecular sieve is an excellent and widely used catalyst with the advantages of strong stability, adjustable pore structure rules, rich acid sites, and good product selectivity.
[0005] Liquid oxygenated fuels mainly include: They have stable chemical properties and are alcohol organics widely used in food, health products, cosmetics and other fields. They can be used as organic reagents and can also be used to produce other chemicals. They are important chemical raw materials. In the pharmaceutical field, these saturated alcohol products are often used as pharmaceutical intermediates for organic synthesis. In addition, they can also be used as intermediates for emerging cycloalkane biofuels and are an attractive fuel blending agent in jet and naval fuels.
[0006] Chinese invention patent CN112341312B discloses a method for preparing cyclohexanol and its derivatives by selective hydrogenolysis of lignin, using organic soluble lignin as raw material, water as reaction solvent, and then using ruthenium-loaded hydrotalcite oxide as catalyst for depolymerization reaction, and solid-liquid separation to obtain a product mixture containing cyclohexanol and its derivatives. This technical embodiment is carried out at 280°C, H 2 Under the condition of 4MPa pressure, the reaction lasted for 8h, and the yield of cyclohexanol and its derivative oxides reached 9.42wt%, the selectivity of cyclohexanol was 18.9%, and the selectivity of 4-ethylcyclohexanol was 40.2%. However, this technology is a long-term reaction under high pressure, and the reaction conditions are relatively harsh. Although hydrotalcite can provide certain alkaline sites, it lacks sufficient acidic sites, and the catalytic effect of lignin depolymerization is relatively limited.
[0007] Chinese invention patent CN118771960A relates to a method for preparing cyclohexanol by depolymerization and catalytic hydrogenation of lignin. The preparation method of this technology is divided into three steps: depolymerization reaction of lignin with sodium hydroxide solution, cooling to room temperature after the reaction is completed, separating the liquid product from the solid residue, extracting the liquid product with ethyl acetate, separating the extract, and collecting phenol and guaiacol; adding phenol, ultrapure water and 5wt% Pd / AC catalyst to a high-pressure reactor, and introducing hydrogen to carry out catalytic hydrogenation reaction to prepare cyclohexanol; adding guaiacol, ultrapure water and 5wt% Ru / AC catalyst to a high-pressure reactor, and introducing hydrogen to carry out catalytic hydrogenation reaction to prepare cyclohexanol. Although it can make lignin selectively generate phenolic compounds under mild conditions and achieve efficient conversion of cyclohexanol at room temperature, its preparation method is cumbersome and has a long preparation cycle. In addition, the alkaline sodium hydroxide solution used in the first step of lignin depolymerization will cause certain corrosion to the reaction equipment (reactor), shortening the service life of the equipment. In addition, the waste alkali liquid after the reaction requires additional treatment to avoid alkaline pollution to water and soil, which also increases the complexity and cost of the process. Summary of the invention
[0008] The object of the present invention is to provide an environmentally friendly, high-efficiency hydrogenolysis catalyst that does not require additional reduction, and a method for catalyzing the selective hydrogenolysis of lignin to prepare C6-C9 liquid oxygen-containing fuels, wherein the catalyst acidity and alkalinity, reduction temperature and other properties are regulated by changing the doping amount of magnesium oxide and the loading amount of hydrated ruthenium, so as to achieve efficient depolymerization of lignin. In the method, the conversion rate of lignin can reach up to 92.6-97.8%, the total yield of volatile products can reach 25.6-36.2%, the total yield of alcohol products can reach 16.5-20.2%, the selectivity can reach 49.5-59.7%, and the yield of 4-ethylcyclohexanol can reach 9.6-13.4%.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin: using lignin as raw material, adding a hydrated ruthenium-based catalyst and an alcohol solvent into the raw material, reacting for 2-6 hours at a H2 pressure of 1-4 MPa and 190-290°C, depolymerizing the lignin to obtain a C6-C9 liquid oxygen-containing fuel; the hydrated ruthenium-based catalyst is expressed as HROx-MgOy@TS-1, which is composed of a carrier TS-1, an alkaline auxiliary agent MgO and an active component hydrated ruthenium, wherein HRO is a ruthenium complex composed of Ru(OH)3, RuO2 and bonded water molecules, wherein the ruthenium loading x accounts for 3-10% of the total mass of the total catalyst, and the magnesium doping amount y accounts for 5-25% of the total mass of the total catalyst.
[0011] In order to further achieve the purpose of the present invention, preferably, the preparation method of the hydrated ruthenium-based catalyst is: fully dissolving hydrated ruthenium trichloride (RuCl3·xH2O) in deionized water, adding MgOy@TS-1 and stirring, adjusting the pH to 9-10, filtering after 3-5 hours, washing the filter cake and drying it to obtain a hydrated ruthenium-based catalyst solid.
[0012] Preferably, the preparation method of MgOy@TS-1 is as follows: fully dissolve magnesium nitrate (Mg(NO3)2·6H2O) in deionized water, add TS-1 and stir fully, adjust the pH to 11-12, filter, wash and dry after 3-5 hours, and calcine in air to obtain MgOy@TS-1;
[0013] The pH value is adjusted to 9-10 by adding ammonia water;
[0014] The washing of the filter cake after washing and drying is washing with deionized water for 2 to 3 times;
[0015] The temperature for drying the filter cake after washing is 80-100° C., and the drying time is 10-12 hours.
[0016] Preferably, the preparation method of TS-1 is as follows: adding hexadecyltrimethylammonium bromide (CTAB) and a silicon source to deionized water, stirring at 40-50° C. for 4-5 hours, adding tetrapropylammonium bromide after sufficient hydrolysis; adding tetrabutyl titanate dissolved in isopropanol, stirring for 3-4 hours, adjusting the pH to 10-11, standing and aging for 10-12 hours to form a gel; hydrothermally crystallizing the obtained gel at 170-180° C. for 3-4 days, filtering the obtained suspension, washing the obtained filter cake, drying it, and sintering it in air to obtain TS-1;
[0017] The pH value is adjusted to 11-12 by adding ammonia water;
[0018] The temperature of filtering, washing and drying after 3 to 5 hours is 80 to 100° C. and the drying time is 10 to 12 hours;
[0019] The calcination is carried out in a muffle furnace at a temperature of 500-600° C. and a calcination time of 3-5 hours.
[0020] The ratio of magnesium nitrate (Mg(NO3)2·6H2O) to TS-1 is 0.6:1 to 5:1.
[0021] Preferably, the mass ratio of hexadecyltrimethylammonium bromide, tetrapropylammonium bromide, silicon source and tetrabutyl titanate is 4:8:25:1 to 8:10:30:1;
[0022] The adjustment of pH to 10-11 is achieved by adding ethylamine or ammonia water;
[0023] The method of washing and drying the obtained filter cake is to wash the obtained filter cake with ethanol for 2 to 3 times and then place it in an oven at 100 to 120° C. to dry it;
[0024] The silicon source is tetraethyl silicate or silica sol.
[0025] Preferably, the mass ratio of lignin to the hydrated ruthenium-based catalyst is 1:0.2 to 1:1.2, and the mass ratio of lignin to the alcohol solvent is 1:10 to 1:20.
[0026] Preferably, the alcohol solvent is any one of methanol, ethanol and isopropanol.
[0027] Preferably, the lignin is derived from any one of bagasse, poplar, bamboo, straw and corn cob.
[0028] Preferably, the lignin is extracted by the following method: adding the lignin raw material and the extracting solution into a reactor, reacting at 100-120° C. for 2-6 hours, and then filtering and separating; adding deionized water to the filtrate, filtering to obtain a solid, and drying to obtain an organic soluble lignin; the extracting solution is composed of adding 3000-4000 mL of anhydrous ethanol and 800-1000 mL of deionized water to every 20-25 g of concentrated sulfuric acid, and adding 120-150 mL of the extracting solution to every 10.0 g of lignin raw material.
[0029] Preferably, the C6-C9 liquid oxygen-containing fuel is one or more of cyclohexanol, 4-methylcyclohexanol, 4-ethylcyclohexanol and 4-propylcyclohexanol.
[0030] Compared with other lignin catalytic depolymerization technologies, the present invention has the following characteristics:
[0031] (1) The present invention is based on the current problems of low lignin depolymerization conversion rate and low product yield. By adding magnesium oxide, the alkalinity and other properties of the supported catalyst are improved. Through acid-base synergy, the CO bond in lignin can be efficiently broken, and a highly selective saturated alcohol product is obtained.
[0032] (2) The hydrated ruthenium catalyst of titanium silicon molecular sieve doped with magnesium oxide used in the present invention has excellent catalytic activity. The incorporation of magnesium oxide makes it easier for hydrated ruthenium to be reduced to active ruthenium species, and at the same time adjusts the overall acidity and alkalinity of the catalyst, so that it has suitable acid-base sites, further enhancing the catalytic activity.
[0033] (3) The catalyst used in the present invention is prepared by adding a hexadecyl trimethyl ammonium bromide solution as a template, thereby obtaining a multi-level pore molecular sieve material containing a large number of micropores and mesopores. This pore structure is conducive to the mass transfer of lignin macromolecules, thereby improving its reaction activity.
[0034] (4) The catalyst used in the present invention can efficiently catalyze the hydrogenolysis of lignin and has a high selectivity for saturated alcohol products. The conversion rate of lignin can reach up to 92.6-97.8%, the total yield of volatile products can reach 25.6-36.2%, the total yield of alcohol products can reach 16.5-20.2%, the selectivity can reach 49.5-59.7%, and the yield of 4-ethylcyclohexanol can reach 9.6-13.4%.
[0035] (5) The catalyst preparation process used in the present invention is simple, energy-saving, does not require additional reduction, and has little environmental pollution. The reaction conditions for lignin depolymerization are mild, and a high yield of saturated alcohols can be obtained at a reaction pressure of 1 to 4 MPa and a reaction temperature of 190 to 290°C, which is conducive to reducing energy consumption and achieving lignin depolymerization under mild conditions.
[0036] (6) The catalyst used in the present invention can efficiently catalyze the hydrogenolysis of lignin and has a high selectivity for saturated alcohol products. The high selectivity of the catalyst for such high value-added chemicals is not only conducive to reducing the occurrence of side reactions, but also can reduce the difficulty of separating the target product. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The XRD patterns of the TS-1 carrier and MgO-doped TS-1 in Example 1 of the present invention are shown in FIG.
[0038] Figure 2 N is the TS-1 carrier and MgO doped TS-1 in Example 1 of the present invention. 2 Physical adsorption-desorption isotherms.
[0039] Figure 3 This is the pore size distribution diagram of the TS-1 carrier and MgO-doped TS-1 in Example 1 of the present invention.
[0040] Figure 4 These are SEM images of the TS-1 carrier and MgO-doped TS-1 in Example 1 of the present invention.
[0041] Figure 5 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention x -MgO y @XRD pattern of TS-1 catalyst.
[0042] Figure 6 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention x -MgO y @TS-1 catalyst N 2 Physical adsorption-desorption isotherms.
[0043] Figure 7 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention x -MgO y @Pore size distribution diagram of TS-1 catalyst.
[0044] Figure 8 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention 5 -MgO 20 @SEM image of TS-1 catalyst.
[0045] Fig. 9 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention 5 -MgO 20@TEM and EDS Mapping of TS-1 catalyst.
[0046] Fig.10 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention 5 -MgO 20 Ru3d spectrum in the XPS spectrum of @TS-1 catalyst.
[0047] Fig.11 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention 5 -MgO 20 Mg2p spectrum in the XPS spectrum of @TS-1 catalyst.
[0048] Fig.12 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention 5 -MgO 20 @TG-MS spectrum of TS-1 catalyst.
[0049] Fig.13 FT-IR spectrum of hydrated ruthenium HRO in Example 1 of the present invention.
[0050] Fig.14 The titanium silicon molecular sieve doped with magnesium oxide-supported hydrated ruthenium-based HRO in Example 1 of the present invention x -MgO y @TS-1 catalyst H 2 -TPR diagram.
[0051] Fig.15 The titanium silicon molecular sieve doped with magnesium oxide supported hydrated ruthenium-based HRO in Examples 1 to 3 of the present invention x -MgO y @TS-1 catalyst CO 2 -TPD graph.
[0052] Fig.16 The titanium silicon molecular sieve doped with magnesium oxide supported hydrated ruthenium-based HRO in Examples 1 to 3 of the present invention x -MgO y @TS-1 catalyst NH 3 -TPD graph.
[0053] Fig.17 is HRO in Example 9 of the present invention 5 -MgO 20 @GC-MS-FID spectrum of the products obtained by TS-1 catalyzed organolytic lignin dissolution. DETAILED DESCRIPTION
[0054] For a better understanding of the present invention, the present invention will be further described below with reference to the accompanying drawings and embodiments, but the embodiments of the present invention are not limited thereto.
[0055] The C6-C9 liquid oxygen-containing fuel product of the present invention refers to one or more of cyclohexanol, 4-methylcyclohexanol, 4-ethylcyclohexanol and 4-propylcyclohexanol. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin of the present invention is to use lignin as raw material, add a hydrated ruthenium-based catalyst and an alcohol solvent to the raw material, and then 2 The reaction is carried out at a pressure of 1 to 4 MPa and 190 to 290°C for 2 to 6 hours to depolymerize the lignin to obtain C6 to C9 liquid oxygen-containing fuel.
[0056] The core feature of the present invention is the use of a hydrated ruthenium-based catalyst, which is expressed as HRO x -MgO y @TS-1, composed of carrier TS-1, alkaline auxiliary agent MgO and active component hydrated ruthenium, HRO is composed of Ru(OH) 3 、RuO 2 The preparation method of the hydrated ruthenium-based catalyst is relatively simple. The hydrated ruthenium trichloride (RuCl 3 ·xH 2 O) was fully dissolved in deionized water and MgO was added y @TS-1 and stir, adjust the pH to 9-10, filter after 3-5 hours, wash the filter cake and dry it. y @TS-1 can be obtained by referring to relevant technical measures, magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) is fully dissolved in deionized water, TS-1 is added and stirred fully, the pH is adjusted to 11-12, filtered, washed, dried after 3-5 hours, and calcined in air to obtain. TS-1 is available in the prior art, and can also be preferably prepared by the following method: add hexadecyltrimethylammonium bromide (CTAB) and silicon source into deionized water, stir at 40-50°C for 4-5 hours, add tetrapropylammonium bromide after sufficient hydrolysis; add tetrabutyl titanate dissolved in isopropanol, stir for 3-4 hours, adjust the pH to 10-11, and stand for aging for 10-12 hours to form a gel; the obtained gel is hydrothermally crystallized at 170-180°C for 3-4 days, the obtained suspension is filtered, the obtained filter cake is washed, dried, and sintered in air. As for the relevant adjustment of pH, washing, and drying, they can be obtained on the basis of the prior art in combination with the purpose of the invention.
[0057] In the technical measures of the present invention, the alcohol solvent medium is an excellent hydrogen donor due to its own hydroxyl group, and can also promote the reaction of solvent and H 2 The hydrogen exchange between them is beneficial to the breaking of CO bonds in lignin. It is important that the hydrated ruthenium-based catalyst HRO used in the present invention x -MgO y @TS-1 is composed of carrier TS-1, alkaline auxiliary agent MgO and active component hydrated ruthenium, wherein the loading amount of ruthenium is x, which means that Ru accounts for 3-10wt.% of the total mass of the total catalyst, and the doping amount of magnesium is y, which means that the mass of Mg accounts for 5-25wt.% of the total mass of the total catalyst. The strong synergistic effect between the acidic sites of the carrier TS-1 of the catalyst and the alkaline sites of the auxiliary agent MgO can enhance the ability to break the connecting bonds between the basic structural units of lignin. In addition, the alkaline sites are conducive to demethoxylation and selective retention of hydroxyl groups, thereby facilitating further hydrogenation and deoxygenation of small molecule intermediates to generate liquid oxygen-containing fuel products. Therefore, a method for preparing C6-C9 liquid oxygen-containing fuels by selective hydrogenolysis of lignin of the present invention is to use lignin as a raw material, add a hydrated ruthenium-based catalyst and an alcohol solvent to the raw material, and control the process conditions H 2 When the pressure is 1-4 MPa and the reaction temperature is 190-290°C for 2-6 hours, the lignin can be depolymerized to obtain liquid oxygen-containing fuel products.
[0058] Preferably, the alcohol solvent can be any one of methanol, ethanol and isopropanol; the lignin can be derived from any one of bagasse, corn stalks, poplar and bamboo; the mass ratio of lignin to hydrated ruthenium-based catalyst is 1:0.2 to 1:1.2; the mass ratio of lignin to alcohol solvent is 1:10 to 1:20.
[0059] The lignin extraction method of the present invention is basically a method disclosed in the prior art, specifically, adding a lignin raw material and an extracting solution into a reaction kettle, reacting at 100-120°C for 2-6 hours, and then filtering and separating; adding deionized water to the obtained filtrate, filtering to obtain a solid, and drying to obtain an organic soluble lignin; the extracting solution is composed of a mixture of concentrated sulfuric acid, anhydrous ethanol and deionized water; the mass concentration of the concentrated sulfuric acid is 95-98%, 3200-4000mL of anhydrous ethanol and 800-1000mL of deionized water are added to every 24g of concentrated sulfuric acid; and 120-150mL of the extracting solution is added to every 10.0g of the lignin raw material.
[0060] Example 1: HRO 5 -MgO 20 Preparation of @TS-1 catalyst
[0061] Hydrated Ruthenium Catalyst HRO Doped with Titanium Silica Molecular Sieve and Supported by Magnesium Oxide 5 -MgO 20The preparation of @TS-1 is achieved through a three-step process:
[0062] (1) The preparation method of carrier TS-1 is as follows: 2.915 g of hexadecyltrimethylammonium bromide (CTAB) and 17.7 ml of tetraethyl silicate are weighed respectively and added to 27 ml of deionized water, stirred at 40°C for 5 h, and after sufficient hydrolysis, 10.65 g of tetrapropylammonium bromide is added; 0.68 ml of tetrabutyl titanate is fully dissolved in 6.5 ml of isopropanol, slowly dripped into the above solution and stirred for 3 h, 7.8 g of 70% by mass ethylamine is added to adjust the pH to 10, and the solution is aged for 12 h. The above gel is placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, and hydrothermally crystallized at 170°C for three days, then filtered, washed with ethanol, dried, and calcined in air to obtain a white solid, which is a multi-level porous TS-1 (titanium silicate molecular sieve).
[0063] (2)MgO 20 The preparation method of @TS-1 is as follows: 1.06 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) was fully dissolved in deionized water, 0.3 g TS-1 was added and stirred thoroughly, and an appropriate amount of ammonia was added to adjust the pH to 11. After 4 hours, it was filtered, washed and dried, and calcined in a muffle furnace at 550 ° C for 4 hours to obtain MgO 20 @TS-1.
[0064] The prepared TS-1 carrier and MgO 20 @TS-1 was characterized by X-ray diffraction to explore its crystal structure. The results are as follows Figure 1 The prepared catalyst has a typical MFI topological structure, and obvious diffraction peaks are observed at 7.68°, 8.60°, 12.94°, 13.66°, 14.48°, 15.60°, 17.53°, 20.54°, 22.77°, 23.65°, 26.61°, and 29.60°, which are respectively attributed to the (101), (200), (002), (102), (301), (022), (400), (103), (501), (303), (600), and (503) crystal planes of TS-1. However, due to the low content of MgO and its uniform dispersion on TS-1, no relevant characteristic diffraction peaks are observed.
[0065] The prepared TS-1 carrier and MgO 20 @TS-1 for N 2 Physical adsorption and desorption characterization was used to explore its pore structure. The results are as follows Figure 2 and Figure 3 As shown. Figure 2It can be seen that the adsorption isotherms of both are typical type IV isotherms, and in the medium relative pressure range (P / P 0 =0.4~1.0) an obvious H4 type hysteresis loop can be observed, indicating that the carrier has a mesoporous structure. Figure 3 From the pore size distribution diagram, it can be seen that the main pore structure of the carrier is mesopores of 2 to 3 nm and micropores of 0.5 to 1 nm. Compared with pure TS-1, its mesopore content is reduced after doping with MgO.
[0066] The prepared TS-1 carrier and MgO 20 @TS-1 was subjected to SEM characterization to explore its surface morphology. The results are as follows Figure 4 As shown, it can be clearly observed that the surface morphology of the carrier is a regular cubic prism, and the surface morphology of the catalyst does not change significantly after doping with MgO.
[0067] (3) HRO 5 -MgO 20 @TS-1 catalyst preparation: weigh 0.0324g RuCl 3 ·xH 2 O solid and dissolved in 150 ml of deionized water, the solution was added into a 20 In the beaker of @TS-1, drop an appropriate amount of ammonia water to adjust the solution pH to 10, stir vigorously for 4 hours, filter, wash three times with deionized water, and then place the mixture in an oven at 80°C to dry. After drying, grind the sample into powder. The resulting solid is HRO 5 -MgO 20 @TS-1.
[0068] The prepared HRO 5 -MgO 20 The TS-1 catalyst was characterized by X-ray diffraction to explore its phase structure. Figure 5 The results show that the catalyst loaded with hydrated ruthenium has obvious diffraction peaks at 12.94°, 13.66°, 14.48°, 15.60°, 17.53°, 20.54°, 22.77°, 23.65°, 26.61°, and 29.60°, indicating that the carrier TS-1 still maintains the original phase structure, while HRO has no relevant diffraction peaks. The HRO recovered after catalyzing the hydrogenolysis reaction of lignin 5 -MgO 20 @TS-1 catalyst has a new diffraction peak at 43.4°, corresponding to the (101) crystal plane of elemental Ru, and HRO 5 -MgO 20 During the reaction, the high-valent Ru in the @TS-1 catalyst was in situ reduced to zero-valent ruthenium. Compared with the same loading of Ru / TS-1 and Ru5 -MgO 20 @TS-1, the diffraction peak intensity is weak, which is because the in-situ reduced Ru is more evenly dispersed on the catalyst.
[0069] The prepared HRO 5 -MgO 20 @TS-1 catalyst for N 2 Physical adsorption and desorption characterization was used to explore its pore structure. The results are as follows Figure 6 and Figure 7 As shown. Figure 6 It can be seen that the adsorption isotherms of each catalyst are typical type IV isotherms, and in the medium relative pressure range (P / P 0 =0.4~1.0) an obvious H4 type hysteresis loop can be observed, indicating that the carrier has a mesoporous structure. Figure 7 The pore size distribution diagram shows that the main pore structure of the carrier is 2-3 nm mesopores and 0.5-1 nm micropores, which is smaller than that of TS-1 carrier and MgO 20 @TS-1, the micropore content is reduced after loading HRO.
[0070] The prepared HRO 5 -MgO 20 @TS-1 catalyst was characterized by SEM to explore its surface morphology. Figure 8 Compared with the TS-1 support, the surface smoothness of the catalyst was observed to be reduced, which was attributed to the supported hydrated ruthenium component.
[0071] The prepared HRO 5 -MgO 20 @TS-1 catalyst was characterized by TEM and EDS Mappig. The results are as follows Fig. 9 As shown, HRO can be observed 5 -MgO 20 @TS-1 has lattice spacings of 1.084, 0.315, and 0.265, corresponding to the (101) crystal plane of TS-1, RuO 2 The (110) crystal plane of MgO and the (111) crystal plane of MgO, the EDS mapping shows that the Mg and Ru elements are well dispersed on the catalyst surface, combined with N 2 The results of physical adsorption and desorption show that in addition to HRO and MgO loaded on the surface, some of them enter the pores and affect the pore structure.
[0072] The prepared HRO 5 -MgO 20 @TS-1 catalyst was characterized by XPS. Fig.10 For fresh HRO 5-MgO 20 @TS-1 catalyst and HRO after a catalytic lignin hydrogenolysis reaction 5 -MgO 20 @The Ru3d spectrum of TS-1 catalyst, such as Fig.10 As shown, the fresh catalyst has four obvious characteristic peaks at 281.6, 282.7, 286.3, and 288.7 eV, corresponding to Ru 4+ 3d 5 / 2 、Ru 3+ 3d 5 / 2 、Ru 4+ 3d 3 / 2 And Ru 3+ 3d 3 / 2 Spin orbit, fresh HRO visible 5 -MgO 20 @TS-1 catalyst contains two valence states: trivalent and tetravalent. After one catalytic lignin hydrogenolysis reaction, HRO 5 -MgO 20 @Ru in TS-1 catalyst 3+ 3d 5 / 2 、Ru 3+ 3d 3 / 2 The characteristic energy spectrum peaks disappeared, and Ru was shown at 280.5 and 285.3. 0 3d 5 / 2 、Ru 0 3d 3 / 2 The energy spectrum peaks indicate that the Ru in the catalyst is the main 3+ Reduction to Ru 0 .
[0073] Fig.11 For HRO 5 -MgO 20 @TS-1 catalyst Mg2p spectrum, which has only one peak at 48 eV, attributed to Mg 2+ , combined with Fig. 9 EDS-Mapping observed the presence and distribution of Mg on HRO-MgO@TS-1, and TEM also observed a lattice spacing of 0.265 nm in the catalyst, which just corresponds to the (111) crystal plane of MgO. The above characterizations prove the presence of MgO in the catalyst.
[0074] Fig.12 About HRO 5 -MgO 20 Thermogravimetric analysis of @TS-1 catalyst showed that the weight loss in the temperature range of 50-200 °C was attributed to the physically adsorbed H 2O molecules, while the weight loss in the temperature range of 200-350 °C is attributed to the chemically bonded H 2 O molecules, HRO 5 -MgO 20 @TS-1 has a weight loss peak at around 223°C, with a weight loss percentage of 3.81%. Mass spectrometry analysis shows that the molecular weight of the lost molecule is 18, which is attributed to the removal of chemically bonded water in HRO, indicating the hydration form of HRO.
[0075] Infrared analysis of HRO, such as Fig.13 As shown, 3428cm -1 The stretching vibration of -OH is attributed to that of RuO 2 , HRO at 3428cm -1 The absorption peak intensity at is significantly higher, which is attributed to the Ru(OH) in HRO. 3 With chemically bonded water.
[0076] The prepared catalyst was subjected to H 2 -TPR characterization, the results are as follows Fig.14 HRO 5 @TS-1 has a peak at 120℃ and 300℃, which are respectively attributed to Ru 3+ With Ru 4+ When doped with 10wt.% MgO, the two reduction peaks of HRO on the catalyst shifted toward the low temperature direction, which indicates that Mg doping helps the reduction of HRO. When doped with 20wt.% MgO, the reduction peaks further shifted toward the low temperature direction, and Ru 3+ The reduction peak shift of MgO is greater because the electronic effect between MgO and HRO makes HRO easier to reduce. The in-situ reduction of HRO at a lower temperature is beneficial to improve the dispersion of Ru species and reduce the aggregation of Ru particles. 3 -MgO 20 @TS-1 has the lowest reduction temperature. This is because when the MgO doping amount is constant, the less the HRO content, the stronger the electronic effect on HRO, and therefore the easier it is to reduce.
[0077] Combination Fig. 9 TEM, Fig.12 TG, Fig.13 FT-IR, Fig.14 H 2 -TPR and other characterizations show that HRO is composed of Ru(OH) 3 、RuO 2 and complexes consisting of chemically bonded water.
[0078] The prepared catalyst was subjected to NH 3-TPD characterization to explore its acidity, the results are as follows Fig.15 All samples can obtain 4 NH 3 Desorption peak, NH 3 -TPD can be divided into three temperature ranges. The desorption peak below 150°C corresponds to weak acid sites, the desorption peak between 150-350°C corresponds to medium-strong acid sites, and the desorption peak above 350°C corresponds to strong acid sites. The results show that when the MgO doping amount is low, the acid site distribution of the catalyst is mostly medium-strong acid sites (desorption peaks B and C) and some weak acid sites (desorption peak A) and strong acid sites (desorption peak D), which shows that TS-1 can provide abundant acid sites. With the increase of MgO doping amount, desorption peaks C and D tend to shift to low temperature and then stabilize in a certain temperature range. At the same time, the areas of the two gradually decrease. The strong acid sites disappear until the MgO doping amount is 25wt.%, and within a certain range of MgO doping amount, the areas of desorption peaks A and B tend to increase, which shows that the doping of MgO will weaken HRO to a certain extent. 5 -MgO x @TS-1 catalyst has a relatively rich acidic site when the MgO doping amount is 20wt.%, and the proportion of medium-strong acidic sites in the total acidic sites is relatively high.
[0079] The prepared catalyst was subjected to CO 2 -TPD characterization to explore its alkalinity, the results are as follows Fig.16 CO 2 -TPD can be divided into two temperature ranges. The desorption peak below 350℃ corresponds to the weak base site, and the desorption peak between 350℃ and 600℃ corresponds to the medium-strong base site. All catalysts have a weak base peak A, which is 3 -TPD characterization results are similar. With the increase of MgO doping amount, a medium-strong alkaline peak B appears at 350℃, and it has a tendency to shift toward high temperature, indicating that MgO mainly provides medium-strong alkaline sites for the catalyst, and with the increase of MgO doping amount, the acidity of the catalyst has less and less effect on the alkaline sites. When the MgO doping amount is 20wt.%, HRO 5 -MgO 20 @TS-1 has the most abundant basic sites.
[0080] Example 2: HRO 5 -MgO 5 Preparation of @TS-1 catalyst
[0081] Hydrated Ruthenium Catalyst HRO Doped with Titanium Silica Molecular Sieve and Supported by Magnesium Oxide 5 -MgO 5 The preparation of @TS-1 is achieved through a three-step process:
[0082] (1) Preparation of TS-1 carrier: 2.915 g of hexadecyltrimethylammonium bromide (CTAB) and 17.7 ml of tetraethyl silicate were weighed separately and added to 27 ml of deionized water, stirred at 40°C for 5 h, and after sufficient hydrolysis, 10.65 g of tetrapropylammonium bromide was added; 0.68 ml of tetrabutyl titanate was fully dissolved in 6.5 ml of isopropanol, slowly dripped into the above solution and stirred for 3 h, 7.8 g of 70% by mass ethylamine was added to adjust the pH to 10, and the gel was allowed to stand for 12 h. The gel was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner and hydrothermally crystallized at 170°C for three days. It was then filtered, washed with ethanol, dried, and calcined in air to obtain a white solid, which was the multi-level porous TS-1.
[0083] (2)MgO 5 Preparation of @TS-1: 0.19 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) was fully dissolved in deionized water, 0.3 g TS-1 was added and stirred thoroughly, and an appropriate amount of ammonia was added to adjust the pH to 11. After 4 hours, it was filtered, washed and dried, and calcined in a muffle furnace at 550 ° C for 4 hours to obtain MgO 5 @TS-1.
[0084] (3) HRO 5 -MgO 5 Preparation of @TS-1 catalyst: 0.0324 g of hydrated ruthenium trichloride (RuCl 3 ·xH 2 O) was fully dissolved in 150 ml of deionized water, and 0.3 g of MgO was added. 5 @TS-1 and stir, drop appropriate amount of ammonia water to adjust the pH to 10, filter it after 4 hours, and wash it with deionized water 3 times, place the filter cake in an oven at 80℃ and dry it for 12 hours. After drying, grind the sample into powder, and the obtained solid is HRO 5 -MgO 5 @TS-1.
[0085] Example 3: HRO 5 -MgO 10 Preparation of @TS-1 catalyst
[0086] Hydrated Ruthenium Catalyst HRO Doped with Titanium Silica Molecular Sieve and Supported by Magnesium Oxide 5 -MgO 10 The preparation of @TS-1 is achieved through a three-step process:
[0087] (1) Preparation of TS-1 carrier: 2.915 g of hexadecyltrimethylammonium bromide (CTAB) and 17.7 ml of tetraethyl silicate were weighed separately and added to 27 ml of deionized water, stirred at 40°C for 5 h, and after sufficient hydrolysis, 10.65 g of tetrapropylammonium bromide was added; 0.68 ml of tetrabutyl titanate was fully dissolved in 6.5 ml of isopropanol, slowly dripped into the above solution and stirred for 3 h, 7.8 g of 70% by mass ethylamine was added to adjust the pH to 10, and the gel was allowed to stand for 12 h. The gel was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner and hydrothermally crystallized at 170°C for three days. It was then filtered, washed with ethanol, dried, and calcined in air to obtain a white solid, which was the multi-level porous TS-1.
[0088] (2) 0.42 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) was fully dissolved in deionized water, 0.3 g TS-1 was added and stirred thoroughly, and an appropriate amount of ammonia was added to adjust the pH to 11. After 4 hours, it was filtered, washed and dried, and calcined in a muffle furnace at 550 ° C for 4 hours to obtain MgO 10 @TS-1.
[0089] (3) HRO 5 -MgO 10 Preparation of @TS-1 catalyst: 0.0324 g of hydrated ruthenium trichloride (RuCl 3 ·xH 2 O) was fully dissolved in 150 ml of deionized water, and 0.3 g of MgO was added. 10 @TS-1 and stir, drop appropriate amount of ammonia water to adjust the pH to 10, filter it after 4 hours, and wash it with deionized water 3 times, place the filter cake in an oven at 80℃ and dry it for 12 hours. After drying, grind the sample into powder, and the obtained solid is HRO 5 -MgO 10 @TS-1.
[0090] Example 4: HRO 5 -MgO 15 Preparation of @TS-1 catalyst
[0091] Hydrated Ruthenium Catalyst HRO Doped with Titanium Silica Molecular Sieve and Supported by Magnesium Oxide 5 -MgO 15 The preparation of @TS-1 is achieved through a three-step process:
[0092] (1) Preparation of TS-1 carrier: 2.915 g of hexadecyltrimethylammonium bromide (CTAB) and 17.7 ml of tetraethyl silicate were weighed separately and added to 27 ml of deionized water, stirred at 40°C for 5 h, and after sufficient hydrolysis, 10.65 g of tetrapropylammonium bromide was added; 0.68 ml of tetrabutyl titanate was fully dissolved in 6.5 ml of isopropanol, slowly dripped into the above solution and stirred for 3 h, 7.8 g of 70% by mass ethylamine was added to adjust the pH to 10, and the gel was allowed to stand for 12 h. The gel was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner and hydrothermally crystallized at 170°C for three days. It was then filtered, washed with ethanol, dried, and calcined in air to obtain a white solid, which was the multi-level porous TS-1.
[0093] (2)MgO 15 Preparation of @TS-1 catalyst: 0.70 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) was fully dissolved in deionized water, 0.3 g TS-1 was added and stirred thoroughly, and an appropriate amount of ammonia was added to adjust the pH to 11. After 4 hours, it was filtered, washed and dried, and calcined in a muffle furnace at 550 ° C for 4 hours to obtain MgO 15 @TS-1.
[0094] (3) HRO 5 -MgO 15 Preparation of @TS-1 catalyst: 0.0324 g of hydrated ruthenium trichloride (RuCl 3 ·xH 2 O) was fully dissolved in 150 ml of deionized water, and 0.3 g of MgO was added. 15 @TS-1 and stir, drop appropriate amount of ammonia water to adjust the pH to 10, filter it after 4 hours, and wash it with deionized water 3 times, place the filter cake in an oven at 80℃ and dry it for 12 hours. After drying, grind the sample into powder, and the obtained solid is HRO 5 -MgO 15 @TS-1.
[0095] Example 5: HRO 5 -MgO 25 Preparation of @TS-1 catalyst
[0096] Hydrated Ruthenium Catalyst HRO Doped with Titanium Silica Molecular Sieve and Supported by Magnesium Oxide 5 -MgO 25 The preparation of @TS-1 is achieved through a three-step process:
[0097] (1) Preparation of TS-1 carrier: 2.915 g of hexadecyltrimethylammonium bromide (CTAB) and 17.7 ml of tetraethyl silicate were weighed separately and added to 27 ml of deionized water, stirred at 40°C for 5 h, and after sufficient hydrolysis, 10.65 g of tetrapropylammonium bromide was added; 0.68 ml of tetrabutyl titanate was fully dissolved in 6.5 ml of isopropanol, slowly dripped into the above solution and stirred for 3 h, 7.8 g of 70% by mass ethylamine was added to adjust the pH to 10, and the gel was allowed to stand for 12 h. The gel was placed in a hydrothermal autoclave with a polytetrafluoroethylene liner and hydrothermally crystallized at 170°C for three days. It was then filtered, washed with ethanol, dried, and calcined in air to obtain a white solid, which was the multi-level porous TS-1.
[0098] (2)MgO 25 Preparation of TS-1: 1.56 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) was fully dissolved in deionized water, 0.3 g TS-1 was added and stirred thoroughly, and an appropriate amount of ammonia was added to adjust the pH to 11. After 4 hours, it was filtered, washed and dried, and calcined in a muffle furnace at 550 ° C for 4 hours to obtain MgO 25 @TS-1.
[0099] (3) HRO 5 -MgO 25 Preparation of @TS-1 catalyst: 0.0324 g of hydrated ruthenium trichloride (RuCl 3 ·xH 2 O) was fully dissolved in 150 ml of deionized water, and 0.3 g of MgO was added. 25 @TS-1 and stir, drop appropriate amount of ammonia water to adjust the pH to 10, filter it after 4 hours, and wash it with deionized water 3 times, place the filter cake in an oven at 80℃ and dry it for 12 hours. After drying, grind the sample into powder, and the obtained solid is HRO 5 -MgO 25 @TS-1.
[0100] Example 6: HRO 3 -MgO 20 Preparation of @TS-1 catalyst
[0101] Hydrated Ruthenium Catalyst HRO Doped with Titanium Silica Molecular Sieve and Supported by Magnesium Oxide 3 -MgO 20 The preparation of @TS-1 is achieved through a three-step process:
[0102] (1) The preparation method of carrier TS-1 is as follows: 2.915 g of hexadecyltrimethylammonium bromide (CTAB) and 17.7 ml of tetraethyl silicate are weighed respectively and added to 27 ml of deionized water, stirred at 40°C for 5 h, and after sufficient hydrolysis, 10.65 g of tetrapropylammonium bromide is added; 0.68 ml of tetrabutyl titanate is fully dissolved in 6.5 ml of isopropanol, slowly dripped into the above solution and stirred for 3 h, 7.8 g of 70% by mass ethylamine is added to adjust the pH to 10, and the gel is placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, hydrothermally crystallized at 170°C for three days, and then filtered, washed with ethanol, dried, and calcined in air to obtain a white solid, which is the multi-level porous TS-1.
[0103] (2)MgO 20 The preparation method of @TS-1 is as follows: 1.06 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) was fully dissolved in deionized water, 0.3 g TS-1 was added and stirred thoroughly, and an appropriate amount of ammonia was added to adjust the pH to 11. After 4 hours, it was filtered, washed and dried, and calcined in a muffle furnace at 550 ° C for 4 hours to obtain MgO 20 @TS-1.
[0104] (3) HRO 3 -MgO 20 Preparation of @TS-1 catalyst: 0.0193 g of hydrated ruthenium trichloride (RuCl 3 ·xH 2 O) was fully dissolved in 150 ml of deionized water, and 0.3 g of MgO was added. 20 @TS-1 and stir, drop appropriate amount of ammonia water to adjust the pH to 10, filter it after 4 hours, and wash it with deionized water 3 times, place the filter cake in an oven at 80℃ and dry it for 12 hours. After drying, grind the sample into powder, and the obtained solid is HRO 3 -MgO 20 @TS-1.
[0105] Example 7: HRO 7 -MgO 20 Preparation of @TS-1 catalyst
[0106] Hydrated Ruthenium Catalyst HRO Doped with Titanium Silica Molecular Sieve and Supported by Magnesium Oxide 7 -MgO 20 The preparation of @TS-1 is achieved through a three-step process:
[0107] (1) The preparation method of carrier TS-1 is as follows: 2.915 g of hexadecyltrimethylammonium bromide (CTAB) and 17.7 ml of tetraethyl silicate are weighed respectively and added to 27 ml of deionized water, stirred at 40°C for 5 h, and after sufficient hydrolysis, 10.65 g of tetrapropylammonium bromide is added; 0.68 ml of tetrabutyl titanate is fully dissolved in 6.5 ml of isopropanol, slowly dripped into the above solution and stirred for 3 h, 7.8 g of 70% by mass ethylamine is added to adjust the pH to 10, and the gel is placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, hydrothermally crystallized at 170°C for three days, and then filtered, washed with ethanol, dried, and calcined in air to obtain a white solid, which is the multi-level porous TS-1.
[0108] (2)MgO 20 The preparation method of @TS-1 is as follows: 1.06 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) was fully dissolved in deionized water, 0.3 g TS-1 was added and stirred thoroughly, and an appropriate amount of ammonia was added to adjust the pH to 11. After 4 hours, it was filtered, washed and dried, and calcined in a muffle furnace at 550 ° C for 4 hours to obtain MgO 20 @TS-1.
[0109] (3) HRO 7 -MgO 20 Preparation of @TS-1 catalyst: 0.0482 g of hydrated ruthenium trichloride (RuCl 3 ·xH 2 O) was fully dissolved in 150 ml of deionized water, and 0.3 g of MgO was added. 20 @TS-1 and stir, drop appropriate amount of ammonia water to adjust the pH to 10, filter it after 4 hours, and wash it with deionized water 3 times, place the filter cake in an oven at 80℃ and dry it for 12 hours. After drying, grind the sample into powder, and the obtained solid is HRO 7 -MgO 20 @TS-1.
[0110] Example 8: HRO 10 -MgO 20 Preparation of @TS-1 catalyst
[0111] Hydrated Ruthenium Catalyst HRO Doped with Titanium Silica Molecular Sieve and Supported by Magnesium Oxide 10 -MgO 20 The preparation of @TS-1 is achieved through a three-step process:
[0112] (1) The preparation method of carrier TS-1 is as follows: 2.915 g of hexadecyltrimethylammonium bromide (CTAB) and 17.7 ml of tetraethyl silicate are weighed respectively and added to 27 ml of deionized water, stirred at 40°C for 5 h, and after sufficient hydrolysis, 10.65 g of tetrapropylammonium bromide is added; 0.68 ml of tetrabutyl titanate is fully dissolved in 6.5 ml of isopropanol, slowly dripped into the above solution and stirred for 3 h, 7.8 g of 70% by mass ethylamine is added to adjust the pH to 10, and the gel is placed in a hydrothermal autoclave with a polytetrafluoroethylene liner, hydrothermally crystallized at 170°C for three days, and then filtered, washed with ethanol, dried, and calcined in air to obtain a white solid, which is the multi-level porous TS-1.
[0113] (2)MgO 20 The preparation method of @TS-1 is as follows: 1.06 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) was fully dissolved in deionized water, 0.3 g TS-1 was added and stirred thoroughly, and an appropriate amount of ammonia was added to adjust the pH to 11. After 4 hours, it was filtered, washed and dried, and calcined in a muffle furnace at 550 ° C for 4 hours to obtain MgO 20 @TS-1.
[0114] (3) HRO 10 -MgO 20 Preparation of @TS-1 catalyst: 0.0724 g of hydrated ruthenium trichloride (RuCl 3 ·xH 2 O) was fully dissolved in 150 ml of deionized water, and 0.3 g of MgO was added. 20 @TS-1 and stir, drop appropriate amount of ammonia water to adjust the pH to 10, filter it after 4 hours, and wash it with deionized water 3 times, place the filter cake in an oven at 80℃ and dry it for 12 hours. After drying, grind the sample into powder, and the obtained solid is HRO 10 -MgO 20 @TS-1.
[0115] Example 9: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0116] (1) Extraction of lignin: Weigh 10.0g of bagasse raw material, 120mL of extracting solution, add into 250mL of hydrothermal kettle, and place in an oven at 110℃ for 4h. After cooling to room temperature, filter and wash with ethanol, collect the filtrate and washing solution, add 500mL of deionized water to precipitate lignin. After filtering through a 0.22μm filter membrane, place in a fume hood to air dry, grind into powder to obtain organic soluble bagasse lignin. The extracting solution is composed of 24g of 98% concentrated sulfuric acid, 3200mL of anhydrous ethanol and 800mL of deionized water.
[0117] (2) Catalytic depolymerization of lignin: Weigh 100 mg of the organosoluble bagasse lignin extracted in step (1), 100 mg of HRO 5 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, the air in the reactor was replaced with high-purity hydrogen three times, 2.0MPa hydrogen was filled in, and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and added with internal standard dimethyl phthalate, and 1mL of the reaction solution was analyzed by GC-MS-FID. The reaction solution was filtered to obtain a filtrate, and deionized water was added to 200mL. It was allowed to stand for about 24h to precipitate the unreacted lignin, and the regenerated lignin was obtained after filtration and drying.
[0118] The chromatographic column was 30 m × 0.25 mm × 0.25 μm and the flow rate was 2 mL min-1. -1 , split ratio 4:1. Heating program: 50℃ for 1min, then 10℃min -1 The heating rate was raised to 280°C and maintained for 15 min) to conduct qualitative analysis and quantitative calculation of the product. The GC-MS-FID results of the product are as follows: Fig.17 And as shown in Table 1.
[0119] The calculation results show that in HRO 5 -MgO 20 @TS-1 catalyst, the conversion rate of lignin reached 97.6%, and the total yield of volatile products was 36.2%. Fig.17The retention times of product peaks 2, 4, 5, and 6 of C6-C9 liquid oxygen-containing fuel are 6.5, 7.4, 9.1, and 11.6 min, respectively, corresponding to cyclohexanol, 4-methylcyclohexanol, 4-ethylcyclohexanol, and 4-propylcyclohexanol. The yields of cyclohexanol, 4-methylcyclohexanol, 4-ethylcyclohexanol, and 4-propylcyclohexanol are calculated to be 0.7 wt.%, 1.5 wt.%, 13.4 wt.%, and 11.6 wt.%, respectively. The total yield of C6-C9 liquid oxygen-containing fuel is 20.2 wt.%, and the selectivity is 55.8%, of which the yield of the main product 4-ethylcyclohexanol is 13.4%, and the selectivity of the compound is 37.0%.
[0120] Table 1 Volatile product ownership and yield
[0121]
[0122]
[0123] Example 10: HRO 5 -MgO 5 @TS-1 catalyzes lignin depolymerization
[0124] The difference between this embodiment and embodiment 9 is that:
[0125] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 5 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0126] The calculation results show that the conversion rate of lignin is 92.6%, the total yield of volatile products is 29.1%, the total yield of saturated alcohols is 16.6%, the selectivity is 57.0%, among which the yield of the main product 4-ethylcyclohexanol is 10.8% and the selectivity of this compound is 37.1%.
[0127] Example 11: HRO 5 -MgO 10 @TS-1 catalyzes lignin depolymerization
[0128] The difference between this embodiment and embodiment 9 is that:
[0129] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 10@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0130] The calculation results show that the conversion rate of lignin is 94.0%, the total yield of volatile products is 29.0%, the total yield of saturated alcohols is 16.3%, the selectivity is 56.2%, among which the yield of the main product 4-ethylcyclohexanol is 10.6%, and the selectivity of this compound is 36.5%.
[0131] Example 12: HRO 5 -MgO 15 @TS-1 catalyzes lignin depolymerization
[0132] The difference between this embodiment and embodiment 9 is that:
[0133] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 15 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0134] The calculation results show that the conversion rate of lignin is 97.9%, the total yield of volatile products is 34.9%, the total yield of saturated alcohols is 19.5%, the selectivity is 55.9%, among which the yield of the main product 4-ethylcyclohexanol is 12.8%, and the selectivity of this compound is 36.7%.
[0135] Example 13: HRO 5 -MgO 25 @TS-1 catalyzes lignin depolymerization
[0136] The difference between this embodiment and embodiment 9 is that:
[0137] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 25@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0138] The calculation results show that the conversion rate of lignin is 94.9%, the total yield of volatile products is 30.5%, the total yield of saturated alcohols is 17.4%, the selectivity is 57.0%, among which the yield of the main product 4-ethylcyclohexanol is 11.8%, and the selectivity of this compound is 38.7%.
[0139] Example 14: HRO 3 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0140] The difference between this embodiment and embodiment 9 is that:
[0141] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 3 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0142] The calculation results show that the conversion rate of lignin is 93.6%, the total yield of volatile products is 25.6%, the total yield of saturated alcohols is 14.5%, the selectivity is 56.6%, among which the yield of the main product 4-ethylcyclohexanol is 9.6%, and the selectivity of this compound is 37.5%.
[0143] Example 15: HRO 7 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0144] The difference between this embodiment and embodiment 9 is that:
[0145] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 7 -MgO 20@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0146] The calculation results show that the conversion rate of lignin is 96.4%, the total yield of volatile products is 31.6%, the total yield of saturated alcohols is 17.8%, the selectivity is 56.3%, among which the yield of the main product 4-ethylcyclohexanol is 11.9% and the selectivity of this compound is 37.6%.
[0147] Example 16: HRO 10 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0148] The difference between this embodiment and embodiment 9 is that:
[0149] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 10 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0150] The calculation results show that the conversion rate of lignin is 95.0%, the total yield of volatile products is 30.1%, the total yield of saturated alcohols is 17.2%, the selectivity is 57.1%, among which the yield of the main product 4-ethylcyclohexanol is 10.9% and the selectivity of this compound is 36.2%.
[0151] Example 17: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0152] The difference between this embodiment and embodiment 9 is that:
[0153] Weigh 100 mg of organosoluble bagasse lignin, 20 mg of HRO 5 -MgO 20@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0154] The calculation results show that the conversion rate of lignin is 76.7%, the total yield of volatile products is 17.2%, the total yield of saturated alcohols is 2.1%, and the selectivity is 12.1%. The yield of the main product 4-ethylcyclohexanol is 2.1%, and the selectivity of this compound is 12.1%.
[0155] Example 18: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0156] The difference between this embodiment and embodiment 9 is that:
[0157] Weigh 100 mg of organosoluble bagasse lignin, 40 mg of HRO 5 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0158] The calculation results show that the conversion rate of lignin is 80.8%, the total yield of volatile products is 19.4%, the total yield of saturated alcohols is 10.9%, the selectivity is 55.9%, among which the yield of the main product 4-ethylcyclohexanol is 8.0%, and the selectivity of this compound is 46.5%.
[0159] Example 19: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0160] The difference between this embodiment and embodiment 9 is that:
[0161] Weigh 100 mg of organosoluble bagasse lignin, 60 mg of HRO 5 -MgO 20@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0162] The calculation results show that the conversion rate of lignin is 92.6%, the total yield of volatile products is 22.7%, the total yield of saturated alcohols is 13.9%, the selectivity is 61.3%, among which the yield of the main product 4-ethylcyclohexanol is 10.0%, and the selectivity of this compound is 43.9%.
[0163] Example 20: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0164] The difference between this embodiment and embodiment 9 is that:
[0165] Weigh 100 mg of organosoluble bagasse lignin, 80 mg of HRO 5 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0166] The calculation results show that the conversion rate of lignin is 94.0%, the total yield of volatile products is 26.3%, the total yield of saturated alcohols is 17.5%, the selectivity is 66.4%, among which the yield of the main product 4-ethylcyclohexanol is 10.9% and the selectivity of this compound is 41.4%.
[0167] Example 21: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0168] The difference between this embodiment and embodiment 9 is that:
[0169] Weigh 100 mg of organosoluble bagasse lignin, 120 mg of HRO 5 -MgO 20@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0170] The calculation results show that the conversion rate of lignin is 95.5%, the total yield of volatile products is 30.6%, the total yield of saturated alcohols is 18.3%, the selectivity is 59.9%, among which the yield of the main product 4-ethylcyclohexanol is 11.5%, and the selectivity of this compound is 37.4%.
[0171] Example 22: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0172] The difference between this embodiment and embodiment 9 is that:
[0173] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, the air in the reactor was replaced with high-purity hydrogen three times, 1.0MPa hydrogen was filled in, and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added, and 1mL of the reaction solution was analyzed by GC-MS-FID.
[0174] The calculation results show that the conversion rate of lignin is 95.2%, the total yield of volatile products is 25.6%, the total yield of saturated alcohols is 13.1%, the selectivity is 51.2%, among which the yield of the main product 4-ethylcyclohexanol is 7.7% and the selectivity of this compound is 29.9%.
[0175] Example 23: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0176] The difference between this embodiment and embodiment 9 is that:
[0177] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 20@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, the air in the reactor was replaced with high-purity hydrogen three times, 4.0MPa hydrogen was filled in, and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and added with internal standard dimethyl phthalate, and 1mL of the reaction solution was analyzed by GC-MS-FID.
[0178] The calculation results show that the conversion rate of lignin is 97.8%, the total yield of volatile products is 28.7%, the total yield of saturated alcohols is 14.4%, the selectivity is 50.3%, among which the yield of the main product 4-ethylcyclohexanol is 10.6%, and the selectivity of this compound is 37.1%.
[0179] Example 24: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0180] The difference between this embodiment and embodiment 9 is that:
[0181] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times, and 2.0MPa hydrogen was filled in, and the reaction was carried out at 270°C for 2h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added, and 1mL of the reaction solution was analyzed by GC-MS-FID.
[0182] The calculation results show that the conversion rate of lignin is 95.2%, the total yield of volatile products is 23.6%, the total yield of saturated alcohols is 8.2%, the selectivity is 34.9%, among which the yield of the main product 4-ethylcyclohexanol is 5.4% and the selectivity of this compound is 22.8%.
[0183] Example 25: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0184] The difference between this embodiment and embodiment 9 is that:
[0185] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 20@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times, and 2.0MPa hydrogen was filled in, and the reaction was carried out at 270°C for 6h. After the reaction was completed and cooled to room temperature, the reaction liquid was taken out and added with internal standard dimethyl phthalate, and 1mL of the reaction liquid was analyzed by GC-MS-FID.
[0186] The calculation results show that the conversion rate of lignin is 95.4%, the total yield of volatile products is 28.4%, the total yield of saturated alcohols is 18.3%, the selectivity is 54.9%, among which the yield of the main product 4-ethylcyclohexanol is 10.4%, and the selectivity of this compound is 36.5%.
[0187] Example 26: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0188] The difference between this embodiment and embodiment 9 is that:
[0189] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, the air in the reactor was replaced with high-purity hydrogen three times, 2.0MPa hydrogen was filled in, and the reaction was carried out at 190°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added, and 1mL of the reaction solution was analyzed by GC-MS-FID.
[0190] The calculation results show that the conversion rate of lignin is 91.4%, the total yield of volatile products is 11.4%, the total yield of saturated alcohols is 6.6%, the selectivity is 58.2%, among which the yield of the main product 4-ethylcyclohexanol is 4.4%, and the selectivity of this compound is 38.4%.
[0191] Example 27: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0192] The difference between this embodiment and embodiment 9 is that:
[0193] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 20@TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times. 2.0MPa hydrogen was filled in and the reaction was carried out at 230°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and internal standard dimethyl phthalate was added. 1mL of the reaction solution was taken out for analysis by GC-MS-FID.
[0194] The calculation results show that the conversion rate of lignin is 93.5%, the total yield of volatile products is 20.7%, the total yield of saturated alcohols is 12.2%, the selectivity is 59.0%, among which the yield of the main product 4-ethylcyclohexanol is 7.7% and the selectivity of this compound is 37.0%.
[0195] Example 28: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0196] The difference between this embodiment and embodiment 9 is that:
[0197] Weigh 100 mg of organosoluble bagasse lignin, 100 mg of HRO 5 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, and the air in the reactor was replaced with high-purity hydrogen three times, and 2.0MPa hydrogen was filled in, and the reaction was carried out at 290°C for 4h. After the reaction was completed and cooled to room temperature, the reaction liquid was taken out and added with internal standard dimethyl phthalate, and 1mL of the reaction liquid was analyzed by GC-MS-FID.
[0198] The calculation results show that the conversion rate of lignin is 96.4%, the total yield of volatile products is 33.9%, the total yield of saturated alcohols is 18.2%, the selectivity is 53.9%, among which the yield of the main product 4-ethylcyclohexanol is 12.1% and the selectivity of this compound is 35.8%.
[0199] Example 29: HRO 5 -MgO 20 @TS-1 catalyzes lignin depolymerization
[0200] The difference between this embodiment and embodiment 9 is that:
[0201] (1) Extraction of lignin: Weigh 10.0g of poplar wood raw material, 120mL of extracting solution, add into 250mL of hydrothermal kettle, and place in an oven at 110℃ for 4h. After cooling to room temperature, filter and wash with ethanol, collect the filtrate and washing solution, add 500mL of deionized water to precipitate lignin. After filtering through a 0.22μm filter membrane, place in a fume hood to air dry, grind into powder to obtain organic soluble poplar wood lignin. The extracting solution is composed of 24g of 98% concentrated sulfuric acid, 3200mL of anhydrous ethanol and 800mL of deionized water.
[0202] (2) Catalytic depolymerization of lignin: Weigh 100 mg of the organic poplar lignin extracted in step (1), 100 mg of HRO 5 -MgO 20 @TS-1 catalyst and 20mL isopropanol were placed in a 50mL reactor. The reactor was sealed, the air in the reactor was replaced with high-purity hydrogen three times, 2.0MPa hydrogen was filled in, and the reaction was carried out at 270°C for 4h. After the reaction was completed and cooled to room temperature, the reaction solution was taken out and added with internal standard dimethyl phthalate, and 1mL of the reaction solution was analyzed by GC-MS-FID. The reaction solution was filtered to obtain a filtrate, and deionized water was added to 200mL. It was allowed to stand for about 24h to precipitate the unreacted lignin, and the regenerated lignin was obtained after filtration and drying.
[0203] The calculation results show that the conversion rate of lignin is 91.3%, the total yield of volatile products is 18.3%, the total yield of saturated alcohols is 15.8%, the selectivity is 85.9%, among which the yield of the main product 4-ethylcyclohexanol is 11.0%, and the selectivity of this compound is 59.9%.
[0204] As can be seen from the above examples, the present invention uses a titanium silicon molecular sieve doped with magnesium oxide supported hydrated ruthenium catalyst system to achieve selective hydrogenolysis of lignin. 2 Under the conditions of pressure of 1-4 MPa, reaction temperature of 190-290°C and reaction time of 2-6 h, the conversion rate of lignin is 92.6-97.9%, the total yield of liquid oxygen-containing fuel products can reach 14.4-20.2%, and the yield of 4-ethylcyclohexanol can reach 9.6-13.4%. The titanium silicon molecular sieve doped with magnesium oxide supported hydrated ruthenium catalyst used in the present invention has a simple preparation process, little environmental pollution, is conducive to reducing energy consumption, and realizes the depolymerization of lignin under mild conditions. The saturated alcohol products have stable chemical properties and are alcohol organics widely used in the fields of food, health products, cosmetics, etc. It can be used as an organic reagent and can also be used to produce other chemicals. It is an important chemical raw material, and in the field of medicine, these saturated alcohol products are often used as pharmaceutical intermediates for organic synthesis. In addition, they can also be used as intermediates for emerging cycloalkane biofuels, and are an attractive fuel blending agent in jet and naval fuels.
[0205] Compared with the Chinese invention patent CN112341312B, the titanium silicon molecular sieve doped magnesium oxide supported hydrated ruthenium catalyst of the present invention has the synergistic effect of acidic sites and basic sites, which can significantly improve the selectivity of saturated alcohol products; and it should be noted that the existing catalysts for obtaining saturated alcohol products by lignin degradation are generally difficult to achieve both high yield and selectivity. The present invention can better solve this problem by combining the titanium silicon molecular sieve doped magnesium oxide supported hydrated ruthenium catalyst with alcohol solvent medium. Moreover, the catalyst of the present invention does not need to consume additional H 2 , which can be spontaneously reduced in situ under reaction conditions, saving energy to a certain extent and reducing energy consumption.
[0206] Although Chinese invention patent application CN118771960A can make lignin selectively generate phenolic compounds under mild conditions, and realize the efficient conversion of cyclohexanol at room temperature, its preparation method is cumbersome, and the preparation cycle is long, and the alkaline sodium hydroxide solution used in the first step of the lignin depolymerization process can cause certain corrosion to the reaction unit (reactor), shortening the service life of the equipment, and the waste liquid alkali liquor after the reaction needs additional treatment in addition, to avoid causing alkaline pollution to water and soil, which also increases the complexity and cost of the process. The present invention realizes the directional conversion of lignin in a shorter preparation cycle by a one-step hydrogenolysis reaction, and obtains a highly selective saturated alcohol product. And the raw material properties used in the preparation process of the present invention are stable, not easy to pollute the environment, and the subsequent reaction treatment is simple.
[0207] The catalyst preparation process adopted by the present invention is simple, does not require additional reduction, has little pollution to the environment, realizes the directional conversion of lignin within a relatively short preparation cycle, and obtains highly selective saturated alcohol products.
[0208] The implementation methods of the present invention are not limited to the above-mentioned embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing C6-C9 liquid oxygenated fuel by selective hydrogenolysis of lignin, characterized in that: Lignin is used as a raw material, a hydrated ruthenium-based catalyst and an alcohol solvent are added to the raw material, and the reaction is carried out at a H2 pressure of 1 to 4 MPa and 190 to 290°C for 2 to 6 hours to depolymerize the lignin to obtain a C6 to C9 liquid oxygen-containing fuel; the expression of the hydrated ruthenium-based catalyst is HRO x -MgO y @TS-1, composed of carrier TS-1, alkaline auxiliary agent MgO and active component hydrated ruthenium, HRO is a ruthenium complex composed of Ru(OH)3, RuO2 and bonded water molecules, in which the ruthenium loading x accounts for 3-10% of the total mass of the total catalyst, and the magnesium doping amount is y, accounting for 5-25% of the total mass of the total catalyst.
2. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 1, characterized in that: The preparation method of the hydrated ruthenium-based catalyst is as follows: hydrated ruthenium trichloride is fully dissolved in deionized water, MgO is added y @TS-1 and stir, adjust the pH to 9-10, filter after 3-5 hours, wash the filter cake and dry it to obtain a hydrated ruthenium-based catalyst solid.
3. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 2, characterized in that: The MgO y The preparation method of @TS-1 is as follows: fully dissolve magnesium nitrate in deionized water, add TS-1 and stir thoroughly, adjust the pH to 11-12, filter, wash and dry after 3-5 hours, and calcine in air to obtain MgO y @TS-1; The pH value is adjusted to 9-10 by adding ammonia water; The washing of the filter cake after washing and drying is washing with deionized water for 2 to 3 times; The temperature for drying the filter cake after washing is 80-100° C., and the drying time is 10-12 hours.
4. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 3, characterized in that: The preparation method of TS-1 is as follows: adding hexadecyltrimethylammonium bromide and a silicon source into deionized water, stirring at 40-50°C for 4-5 hours, adding tetrapropylammonium bromide after sufficient hydrolysis; adding tetrabutyl titanate dissolved in isopropanol, stirring for 3-4 hours, adjusting the pH to 10-11, standing and aging for 10-12 hours to form a gel; hydrothermally crystallizing the obtained gel at 170-180°C for 3-4 days, filtering the obtained suspension, washing the obtained filter cake, drying it, and sintering it in air to obtain TS-1; The pH value is adjusted to 11-12 by adding ammonia water; The temperature of filtering, washing and drying after 3 to 5 hours is 80 to 100° C. and the drying time is 10 to 12 hours; The calcination is carried out in a muffle furnace at a temperature of 500-600° C. and a calcination time of 3-5 hours. The ratio of magnesium nitrate to TS-1 is 0.6:1 to 5:
1.
5. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 4, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide, tetrapropylammonium bromide, silicon source and tetrabutyl titanate is 4:8:25:1 to 8:10:30:1; The adjustment of pH to 10-11 is achieved by adding ethylamine or ammonia water; The method of washing and drying the obtained filter cake is to wash the obtained filter cake with ethanol for 2 to 3 times and then place it in an oven at 100 to 120° C. to dry it; The silicon source is tetraethyl silicate or silica sol.
6. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 1, characterized in that: The mass ratio of the lignin to the hydrated ruthenium-based catalyst is 1:0.2-1:1.2, and the mass ratio of the lignin to the alcohol solvent is 1:10-1:
20.
7. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 1, characterized in that: The alcohol solvent is any one of methanol, ethanol and isopropanol.
8. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 1, characterized in that: The lignin is derived from any one of bagasse, poplar, bamboo, straw and corn cob.
9. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 8, characterized in that: The lignin is extracted by the following method: adding the lignin raw material and the extracting solution into a reaction kettle, reacting at 100-120°C for 2-6 hours, and then filtering and separating; adding deionized water to the filtrate, filtering to obtain a solid, and drying to obtain an organic soluble lignin; the extracting solution is composed of adding 3000-4000mL of anhydrous ethanol and 800-1000mL of deionized water to every 20-25g of concentrated sulfuric acid, and adding 120-150mL of the extracting solution to every 10.0g of the lignin raw material.
10. The method for preparing C6-C9 liquid oxygen-containing fuel by selective hydrogenolysis of lignin according to claim 1, characterized in that: The C6-C9 liquid oxygen-containing fuel is one or more of cyclohexanol, 4-methylcyclohexanol, 4-ethylcyclohexanol and 4-propylcyclohexanol.
Citation Information
Patent Citations
A method for selective hydrogenolysis of lignin to prepare cyclohexanol and its derivatives
CN112341312B
Method for preparing cyclohexanol through depolymerization and catalytic hydrogenation of lignin
CN118771960A